Medical medium cleanse to heal ebook Healing plans for sufferers of anxiety, depression, acne, eczema, lyme, gut problems, brain fog, weight issues, migraines, bloating, vertigo, psoriasis. - William, Anthony (2020)
From the #1 New York Times best-selling author of Celery Juice and Liver Rescue , here's everything you need to know about cleansing to transform your health—and your life. If you think you don't have any need to do a cleanse—if you're sure you couldn't possibly be harboring any toxins in your body—think again. In today's world, there are poisons and pathogens that threaten our health starting before we're even born , and they continue to hold us back as we encounter them in our everyday life. Cleansing is a vital tool for fighting against these burdens—as long as you go about it the right way. That's why you need this book. Anthony William, the Medical Medium, has placed a vast wealth of insight and information into a one-stop resource for cleansing of all kinds, starting with his acclaimed nine-day 3:6:9 Cleanse and expanding into life-saving protocols for specific health needs—including an anti-bug cleanse, a morning cleanse, and a heavy metal detox. You'll discover: How to choose the cleanse that's right for you A deep dive into the causes of your symptoms and conditions Critical cleanse dos and don'ts, including modifications and substitutions The truth about trendy topics such as intermittent fasting and the microbiome A guide to supplements you may choose to add to your cleanse The physical reasons why cleansing can be an emotional experience More than 75 recipes and sample menus to get you through your Medical Medium cleanse Spiritual and soul support to remind you that healing is possible "The cleanses in this book speak to what's truly going wrong inside of our bodies that no trendy lifestyle approach can ever address," Anthony writes. "Have compassion for yourself and know that your suffering is not your fault. Your struggles are not your fault. You're accomplishing great things every single hour and day as you work on your healing process with the powerful tools in this book. I believe you can heal."